A COMPILATION OF FACTORS ASSOCIATED TO THE GOVERNANCE AND MANAGEMENT OF AGILE PROJECTS: A SYSTEMATIC LITERATURE REVIEW - Sithambaram, Jayasaegaran; Md Nasir, Mohd Hairul Nizam Bin; Ahmad, Rodina (Malaysian Journal of Computer Science, 2021)
The demand for project success is increasing, while the number of failed projects are still high. Whilst Project Management Offices help in the governance of Information Technology projects, the trending issues and challenges in Agile projects need a great deal of attention. More organisations are embracing the agile method due to its popularity and the benefits it yields. Literature discusses various issues and challenges, with an absence of a holistic review to determine its frequency, impact, and classification systematically. This study attempts to identify the factors addressed in literature over the last 2 decades, producing a list of factors and ranking them according to the most addressed and the frequency of reference. A systematic literature review was undertaken to identify the relevant literature using specific keywords search and filter, arriving at a final list of 175 selected studies for the analysis work, which was used to identify 37 prominent factors affecting agile project success. The highest number of studies and factors discussed were between years 2014 and 2016. Project Governance faired as the most addressed factor, while People related factors were widely discussed. Current trends are focused on attaining project governance with a sound understanding of the agile principles, by people with the right attitude, knowledge, skills, and the ability to work well with the team. Project governance with the careful implementation of the agile method and its processes in stages, with the right support tools and technology, is most important for project success. Competence of project stakeholders possessing the right attitude, with great collaboration and teamwork capabilities, and the ability to garner a close relationship with the customer and clearly articulate changing requirements is key to delivering successful agile projects. Future work will include the understanding and identification of critical challenges and crucial factors for ensuring agile project management success. It is proposed to expand the research further into the project governance and people-related area.